1994
DOI: 10.1007/bf00120336
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of a new flexible polymer with improved cell adhesion

Abstract: An improved cell compatibility of polymers is determined by interactions with the cell surface, which are influenced by the chemical surface properties of the polymers. Of special interest are methods to change the surface properties by generating new functional groups for a better cell adhesion without affecting the bulk properties of the polymer. The study describes the surface modifications of a new flexible copolymer comprising polyvinylchloride by either wet chemical treatment or plasma treatment. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…A number of studies reported the influence of physic-chemistry of the surface toward biological response of viable cells such as hydrophobicity and hydrophilicity of materials 196,198,[325][326][327][328][329][330] . An addition of glycerine was reported to improve the hydrophobicity and lead to a positive biological response of viable cells on the substrate 60,331,332 .…”
Section: Cell Proliferationmentioning
confidence: 99%
“…A number of studies reported the influence of physic-chemistry of the surface toward biological response of viable cells such as hydrophobicity and hydrophilicity of materials 196,198,[325][326][327][328][329][330] . An addition of glycerine was reported to improve the hydrophobicity and lead to a positive biological response of viable cells on the substrate 60,331,332 .…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Although many surface treatments particularly for polymeric materials, e.g., using plasma, corona treatments, etc., have been developed to this end, e.g., to induce hydrophilic/ hydrophobic surfaces etc., and are state of the art, work on coatings that permit specific and local functionalization with persistent effects is still lacking. [9][10][11][12] One might argue that this is already realized in TiO 2 -based materials that can be functionalized using UV irradiation. [13][14][15][16] Unfortunately the properties hitherto achieved, in terms of superhydrophilicity and bactericidity, subside when the UV irradiation is shut-off.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with plasma modified surfaces used different substrates and process conditions, and produced contradictory results [1][2][3][4][5][6]; in addition, there was inadequate chemical characterization of surface composition. The latter is the focus of this study, forming the foundation for the subsequent protein adsorption studies.…”
Section: Introductionmentioning
confidence: 99%